La-Doped biomimetic scaffolds facilitate bone remodelling by synchronizing osteointegration and phagocytic activity of macrophages. Issue 19 (11th April 2019) - Yin, Junhui; Yu, Jianqing; Ke, Qinfei; Yang, Qianhao; Zhu, Daoyu; Gao, Youshui; Guo, Yaping; Zhang, Changqing
Abstract : The capacity of osteoconduction held by HA/CS, osteoinduction by La 3+, and biodegradability by a La-HA/CS composite, contributes to an ideal scaffold for osteointegration and remodelling. Abstract : Rare earth elements (REEs) generally accumulate in natural bone; however, their enhanced effects on stem cell osteogenic differentiation and macrophage phagocytic activity remain to be clarified. Inspired by the components and architectures of natural bone, this was the first study to construct La-doped hydroxyapatite/chitosan (La-HA/CS) biomimetic scaffolds for bone tissue engineering. Intriguingly, the La element in the scaffolds significantly improved the osteogenic differentiation of human bone marrow stromal cells (hBMSCs) and the formation of new bone tissues via an activated Wnt/β-catenin signalling pathway. At the same time, La 3+ ions in the La-HA/CS scaffolds remarkably promoted the proliferation and phagocytic activity of the macrophages, leading to a synchronous biodegradability. The cranial bone defect models of Sprague-Dawley rats further revealed that the La element fantastically synchronizes macrophage-induced biomaterial degradation and new bone formation. The capacity of osteoconduction held by HA/CS, osteoinduction by La 3+, and biodegradability by a La-HA/CS composite, contributes to an ideal scaffold for osteointegration and remodelling. The exciting findings provide a critical and novel strategy to fabricate REE-doped scaffolds for a bone repair strategy.